Additives for Ambient 3D Printing with Visible Light. Issue 44 (14th September 2021) - Ahn, Dowon; Stevens, Lynn M.; Zhou, Kevin; Page, Zachariah A.
Abstract: With 3D printing, the desire is to be "limited only by imagination, " and although remarkable advancements have been made in recent years, the scope of printable materials remains narrow compared to other forms of manufacturing. Light‐driven polymerization methods for 3D printing are particularly attractive due to unparalleled speed and resolution, yet the reliance on high‐energy UV/violet light in contemporary processes limits the number of compatible materials due to pervasive absorption, scattering, and degradation at these short wavelengths. Such issues can be addressed with visible‐light photopolymerizations. However, these lower‐energy methods often suffer from slow reaction times and sensitivity to oxygen, precluding their utility in 3D printing processes that require rapid hardening (curing) to maximize build speed and resolution. Herein, multifunctional thiols are identified as simple additives to enable rapid high‐resolution visible‐light 3D printing under ambient (atmospheric O2 ) conditions that rival modern UV/violet‐based technology. The present process is universal, providing access to commercially relevant acrylic resins with a range of disparate mechanical responses from strong and stiff to soft and extensible. Pushing forward, the insight presented within this study will inform the development of next‐generation 3D‐printing materials, such as multicomponent hydrogels and composites. Abstract : Rapid visible‐light‐induced polymerization of commercially relevant acrylics and concomitant 3D printing under ambient conditions is made possible with thiol additives acting as oxygen scavengers. The tadpole and frog are 3D printed using energy efficient red light‐emitting diodes (LEDs), metaphorically representing the transformative advance that allows additive manufacturing (or breathing for the frog) in air.